TERMINOLOGY MANAGEMENT IN THE TRANSLATION OF OIL AND GAS INDUSTRY DOCUMENTS - Nurmamatova Oysulton Erkinovna; Mirzayeva Gulasal (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION Terminology Management in the Translation of Oil and Gas Industry Documents This article examines the significance of terminology management in the translation of oil and gas industry documents. The oil and gas sector relies heavily on specialized terminology, technical standards, and industry-specific concepts that require accurate and consistent translation. The study investigates the challenges faced by translators when dealing with technical terms, abbreviations, and multilingual documentation. It also analyzes modern terminology management tools, translation memories, and terminology databases that contribute to translation quality and efficiency. The research employs qualitative analysis of technical documents and professional translation practices within the energy sector. The findings demonstrate that effective terminology management enhances translation accuracy, reduces ambiguity, and facilitates international communication among stakeholders in the oil and gas industry.